Effect of titania nanotubes on the differentiation of adipose derived stem cells - Cowden, Kari, author; Dias-Netipanyj, Marcela Ferreira, author; Popat, Ketul C., author (Colorado State University. Libraries, 2017)
Titanium orthopedic implants still experience a high level of failure at the implant site. Earlier studies have shown that nanostructuring the surface of titanium can enhance stem cell migration, proliferation, and differentiation. However, the ideal size of this nanostructuring is still disputed. In this study three distinct diameter controlled nanotube (NT) surfaces were fabricated on titanium sheets using an anodization technique and varied voltages. Adipose-derived stem cells (ADSC) were cultured and proliferation and differentiation was investigated. The results indicate that nanostructed titanium does enhance osseointegration function and furthermore that the nanotube diameter does affect the proliferation and osteodifferentiation of ADSC.
072 - Kari Miller Cowden
Effects of nanotubes on osteogenic differentiation of adipose-derived stem cells